University social responsibility in the current knowledge society: a necessary approach - Rolando Medina Peña; María del Carmen Franco Gómez; Leodanis Torres Barreiro; Kerslin Velázquez Rodríguez; Marina Alexandra Valencia Vera; Ana Leonor Valencia Vera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
In the current times, the connections and dependencies established at all social levels between individuals, institutions, groups and, consequently, the effects of each of the decisions they assume are unquestionable. Each one of them generates certain situations, demands, difficulties, that have a social impact and require a response as coherent and organic as possible, from the personal or institutional position. In this sense, the necessary analysis on responsibility is introduced. This work aims at offering, at first, an approach to social responsibility, a category of vital importance for trust promotion and establishment at all levels of any community. Subsequently, attention is directed towards university social responsibility, identified as a university social dimension. It concludes that the university should be committed to the social surrounding demands, so that its daily practice is in harmony with the context in which it develops.